Dietary supplement use in elementary school children: a Japanese web-based survey - Kazue Ishitsuka; Satoshi Sasaki; Hidetoshi Mezawa; Mizuho Konishi; Maki Igarashi; Kiwako Yamamoto-Hanada; Shoji F. Nakayama; Yukihiro Ohya (Komiyama Printing Co. Ltd, 2021)
Abstract Background A variety of dietary supplements are commercially available. However, the efficacy and safety of dietary supplement use in children are not well established. Understanding dietary supplement use is important for developing public health policy regarding dietary supplements. This study aimed to investigate the types of dietary supplements used and characteristics of dietary supplement users among Japanese elementary school children. Method We conducted a cross-sectional web-based questionnaire study. Dietary supplement use, socio-demographics, and health-related behaviors were assessed through mother-reported questionnaire. Types of dietary supplements were identified based on ingredient using product barcodes and brand names. Multivariate logistic regression analysis was conducted to investigate the socio-demographics and health-related behaviors associated with supplement use. Results Among 4933 children, 333 (6.8%) were identified as dietary supplement users. The most common supplement was amino acids or protein (1.4%), followed by n-3 fatty acids or fish oil (1.0%), probiotics (1.0%), multivitamins (0.9%), multivitamin-minerals (0.8%), and botanicals (0.8%). Overall, any dietary supplement use was significantly associated with the highest frequency of sports participation (odds ratio [OR], 2.58; 95% confidence interval [CI], 1.65-4.02), highest household income (OR, 1.87; 95% CI, 1.13-3.10), highest maternal educational level (OR, 1.82; 95% CI, 1.31-2.52), and male sex (OR, 1.38; 95% CI, 1.09-1.75). The highest frequency of sports participation was significantly associated with higher odds of use of amino acids or protein (OR, 6.06; 95% CI, 1.78-20.6) and multivitamins (OR, 3.56; 95% CI, 1.11-11.5), compared to the lowest frequency of sports participation. Conclusion This study showed that Japanese children primarily use non-vitamin, non-mineral supplements. Non-vitamin, non-mineral supplements should thus be included in future studies aimed at monitoring dietary supplement use. We also found that dietary supplement use in children was associated with sports participation. Guidelines for dietary supplement use for children, in particular sport participants, are needed.